2002
DOI: 10.1111/j.1399-0004.2002.tb02255.x
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic chromosome rearrangements detected by subtelomere assay in patients with mental retardation and dysmorphic features

Abstract: The regions near telomeres of human chromosomes are gene rich. Chromosome subtelomere rearrangements occur with a frequency of 7–10% in children with mild‐to‐moderate mental retardation (MR) and approximately 50% of cases are familial. Clinical investigation of subtelomere rearrangements is now prompted by fluorescence in situ hybridization (FISH) analysis using specific DNA probes from all relevant chromosome ends. In our study, 40 children were selected for subtelomere assay using either the Chromophore Mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 30 publications
0
19
0
1
Order By: Relevance
“…12 First of all, the latter procedure requires a sufficient supply of specimen material and so is particularly difficult when clinical samples are limited in number. Furthermore, the technique requires sophisticated imagecapture analysis to ensure that the correct area from the 24 subregions is selected for counting the correct probes on one slide.…”
Section: Discussionmentioning
confidence: 99%
“…12 First of all, the latter procedure requires a sufficient supply of specimen material and so is particularly difficult when clinical samples are limited in number. Furthermore, the technique requires sophisticated imagecapture analysis to ensure that the correct area from the 24 subregions is selected for counting the correct probes on one slide.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the deletions described here (11/16) were identified by genome-wide array analysis. A large number of previous deletions were reported before genomewide array platforms became common use in routine diagnostic settings, and were either detected by routine FISH or MLPA [Dawson et al, 2002;Cormier-Daire et al, 2003;Font-Montgomery et al, 2004;Iwakoshi et al, 2004;Neas et al, 2005]. Some studies reported fine-mapping of deletions with additional specific 9q probes Stewart et al, 2004].…”
Section: Discussionmentioning
confidence: 99%
“…The syndrome is either caused by a submicroscopic deletion in the chromosomal region 9q34.3 or an intragenic mutation of the euchromatin histone methyltransferase 1 (EHMT1) gene causing haploinsufficiency of EHMT1 . So far, 85 patients, including 75 patients with a 9q34.3 deletion and 10 patients with an EHMT1 mutation, have been reported [Schimmenti et al, 1994;Ayyash et al, 1997;Dawson et al, 2002;Cormier-Daire et al, 2003;Font-Montgomery et al, 2004;Harada et al, 2004;Iwakoshi et al, 2004;Stewart et al, 2004;Neas et al, 2005;Yatsenko et al, 2005Yatsenko et al, , 2009Kleefstra et al, 2006aKleefstra et al, , b, 2009Stewart and Kleefstra, 2007;Verhoeven et al, 2010;Willemsen et al, 2011]. EHMT1 encodes a histone H3 Lys 9 methyltransferase and is thereby involved in chromatin remodeling [Ogawa et al, 2002].…”
mentioning
confidence: 99%
“…Brief descriptions of the syndrome, without photographs, were published in abstract or tabular format shortly after widespread screening for chromosomal subtelomere deletions started in the late 1990s [Anderlid et al, 1999;Knight et al, 1999;Lamb et al, 1999;Rossi et al, 2001]. Dawson et al [2002] provided a detailed description, with photographs, of the syndrome in two unrelated children. They noted some ''phenotypic resemblance'' between the children and similarities to previouslypublished accounts of the syndrome.…”
Section: Clinical Features Diagnosismentioning
confidence: 99%
“…The chromosome 9q subtelomere deletion syndrome (9qSTDS) was one of the first clinically recognizable phenotypes to arise from fluorescent in situ hybridization (FISH) screening of subtelomere deletions and rearrangements [Dawson et al, 2002;Cormier-Daire et al, 2003]. Detailed breakpoint mapping quickly refined the commonly deleted region of the 9qSTDS from 3 Mb [CormierDaire et al, 2003] to 1.2 Mb [Stewart et al, 2004], 1 Mb , and 700 kb [Yatsenko et al, 2005].…”
Section: Introductionmentioning
confidence: 99%